SEJARAH PENIMBUNAN CEKUNGAN SUMATERA SELATAN DAN IMPLIKASINYA TERHADAP WAKTU GENERASI HIDROKARBON - Hermes Panggabean; Lauti Dwita Santy (Jurnal Geologi dan Sumberdaya Mineral, 2012)
South Sumatra Basin is divided into four subbasins, that are Jambi Subbasin, Central Palembang Subbasin, North Palembang Subbasin, and South Palembang Subbasin. Clastic and carbonate sediments had filled the South Sumatra Basin during Eocene up to Quaternary times by various thickness of all rock units in each subbasin ranging from 2100 m to 3500 m. Those four subbasins have shown almost different maximum deep of burial history, that was started from 2900 m up to 5200 m. From burial of maximum depth by over 2000 m, several rock outcrop samples of the Talangakar Formation have evidently compacted, and grain particles as well as minerals of matrix have been proccessed by diagenesis realm. The lowest depth oil generation of the Lahat Formation is 1560 m in the Central Palembang Subbasin, while the deepest in the Talangakar Formation is 2700 in Jambi Subbasin and 2800 m in the South Palembang Subbasin. The timing of hydrocarbon generation has occurred between 20.6 mya (Early Miocene) and 3.38 mya (Late Pliocene). By studying detailed characters of sedimentary rocks filling each subbasin, thus the time of hydrocarbon generation can be known.Keyword : South Sumatra basin, burial history, hydrocarbon generation, Lahat Formation, and Talangakar Formation